Analyse the Study of a Hybrid Power System in the Case of Refrigeration - Swayam Prakash Mohapatra, Sanjay Rathore (Mathematical Statistician and Engineering Applications, 2022)
This study presents the results of an experimental examination into the feasibility of using a solar-wind hybrid power system (HPS) to generate electricity in the Sahara region of Algeria. Most of the power produced has been put toward refrigeration and cooling. A gasoline generator is built into the system as well for added safety. Unlike the military outpost on the Algerian border, this system is not dependent on traditional energy sources or rooted in a specific geographical location. Two "positive" rooms (with an interior temperature of +2 degrees and an external temperature of 35 degrees) and one "negative" room (with an internal temperature of -20 degrees and an outdoor temperature of 35 degrees) made up the cooling load, which required 45 kWh of energy each day to run. Data on sun radiation, temperature, and wind speed for 2010 were gathered at the Adrar weather station (a particularly breezy region of Algeria). HOMER was used to model the HPS (hybrid power system). The major environmental indicator is the percentage of renewable energy generation in relation to total energy consumption. For financial analysis, we compute the net present cost (NPC) and the cost of energy (COE). It has been determined that the best HPS results for Adrar climates result in a 50% reduction in emissions with a 47% renewable energy share.